Retailing in Traditional and Herbal Medicine: Facts and Future - Ghosh, Ashoke K.; Bhattacharya, Sanjib (Pharmacognosy Reviews)
The use of plants and plant-based products in the traetment of diseases is as old as mankind. The plant, animal and mineral products constitute the natural products, which have been the basis of different traditional systems of medicines and practised since time immemorial. These systems are still being practised in developing countries, in recent era even in modern and developed countries, along with modern allopathic medicine. According to WHO (World Health Organization) more than 80% of world’s population still relies on traditional systems of medicine. Several traditional health care systems of medicine are being practised in Indian subcontinent. The most commonly used one are Ayurveda, Siddha and Unani system of medicine. In India, up to several decades ago the medicines used in indigenous systems of medicine were generally prepared and sold by the practicing physicians themselves. In recent decades these practice has been largely replaced by the development of organized herbal drug industry and retail pharmacy. During the course of time, the formulation strategies of traditional medicine have also undergone some changes to cater the needs of today’s patient, to gain the patient’s complience and to improve the product appeal as compared with allopathic medicine. From traditional formulations like decoctions, teas, tinctures, extracts, pills etc, traditional medicines have now been formulated as tablets, capsules, ointment, cream etc. along with age old ayurvedic formulations like fermentation products (Asava, Arishta), decoctions, medicated fats (Ghrita and Taila) etc.